Flexural behaviour of pre-damaged RC beams retrofitted using CFRP laminates - Karuppiah Palaniappan; Philip Saratha Joanna; Murali Rajasekaran; Angeline Prabhavathy; Daniel Cruze; Samuel James (Advances in Civil and Architectural Engineering, 2025)
This study entailed an investigation on retrofitting methods, aimed at enhancing the strength of reinforced concrete (RC) beams by applying carbon fibre-reinforced polymer (CFRP) laminates and CFRP fabrics in the flexural and shear zones of damaged RC beams. The experimental examination involved the casting and subsequent strengthening of six rectangular RC beams, via external bonding techniques utilizing both CFRP laminates and fabrics. The research design included five distinct systems of strengthening of pre-damaged RC beams up to the ultimate load level and 90 % of the ultimate load level. All RC beams were cast using M20-grade concrete and uniform reinforcement detailing. The results revealed a significant enhancement in the load-bearing capacity of the RC beams externally strengthened u CFRP laminates. Particularly, the beams retrofitted with U-shaped wrapping exhibited a substantial improvement in both crack and ultimate loads. These findings underscore the efficacy of the CFRP retrofitting approach, demonstrating a positive impact on the overall structural performance of pre-damaged RC beams. This study indicates that incorporating CFRP laminates and fabrics in the shear and flexural zones of pre-damaged beams up to the ultimate load level can enhance the ultimate load-carrying capacity by up to 13 %. The proposed approach offers a cost-effective strategy to enhance strength and maintain ductility without compromising the overall structural integrity.